2016
DOI: 10.1016/j.trgeo.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale instrumented testing of multiple airfield matting systems on soft soil to characterize permanent deformation

Abstract: This paper presents results from full-scale testing of six airfield matting systems of various materials and designs that were evaluated on subgrades constructed to a California bearing ratio (CBR) of 6 and subjected to simulated aircraft loads. Mat breakage, deformation, and subgrade earth pressure were monitored during each test to determine the effectiveness of the airfield mats in reducing cumulative subgrade deformation and decreasing subgrade stresses.Based on test results, a simplified expression was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…For example, numerous studies have shown that most compaction occurs during the first few machine passes (Ampoorter et al., 2012; Han et al., 2006). The feasibility of using fiberglass mats (e.g., see Garcia & Howard, 2016) before the first pass could be investigated for the hybrid harvesting system used in the current study. It is also important to consider that harvesting occurred during a relatively dry summer compared with 30‐yr climate normal values (Table 2) and that the soils of the study area were excessively to moderately well drained.…”
Section: Discussionmentioning
confidence: 99%
“…For example, numerous studies have shown that most compaction occurs during the first few machine passes (Ampoorter et al., 2012; Han et al., 2006). The feasibility of using fiberglass mats (e.g., see Garcia & Howard, 2016) before the first pass could be investigated for the hybrid harvesting system used in the current study. It is also important to consider that harvesting occurred during a relatively dry summer compared with 30‐yr climate normal values (Table 2) and that the soils of the study area were excessively to moderately well drained.…”
Section: Discussionmentioning
confidence: 99%
“…A basis for this is provided by Garcia and Howard (2016), where the authors developed relationships for predicting subgrade deformation for different mat systems as a function of mat stiffness and F-15E passes. Rushing and Howard (2015) and Rushing and Howard (2017) performed similar work for the AM2 mat system for a range of CBRs.…”
Section: Permanent Deformation Analysismentioning
confidence: 99%
“…Combining the monitoring results with thermal and subsurface conditions, the characteristics and mechanisms of deformation in embankments along the QTR in permafrost regions were determined . Full‐scale monitoring tests of deformation and subgrade earth pressure on six airfield matting systems built with different materials and designs were conducted, and based on an analysis of the results, a formula was proposed to predict subgrade deformation according to aircraft loading and airfield mat properties …”
Section: Introductionmentioning
confidence: 99%
“…13 Full-scale monitoring tests of deformation and subgrade earth pressure on six airfield matting systems built with different materials and designs were conducted, and based on an analysis of the results, a formula was proposed to predict subgrade deformation according to aircraft loading and airfield mat properties. 14 Although considerable researches have been devoted to the monitoring of subgrade deformation in permafrost regions, rather less emphasis has been placed on seasonally frozen soil. Moreover, most existing studies that consider the effects of freezing and thawing on subgrade deformation have been conducted using soil samples or models, in which the boundary conditions adopted are of little practical application.…”
Section: Introductionmentioning
confidence: 99%